The intersection of critical emancipatory peacebuilding and social enterprise - Oloke, Ireoluwatomi (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2018)
The authentic inclusion of members of ethnic minority groups in positive peacebuilding projects allows such groups to develop economic, political, and social capacities essential to their achieving autonomy at the subnational level. This article presents an approach to peacebuilding based on a dialogical theory of action that ensures that the lowest local actors are authentically represented in peacebuilding projects. We develop a dialogical approach to social entrepreneurship that allows for the authentic inclusion of local actors alongside external actors and implementation of a social entrepreneurship project that allows for cooperative involvement. Upon evaluation and in consultation with local actors, the exact form of social entrepreneurship suitable for the community is determined and implemented.
Keywords: avtonomija; dialoška teorija; narodne manjšine; socialno podjetništvo